Niepełnosprawność intelektualna jako peryferie? - Łysik, Barbara (Studia Pastoralne, 2026)
The Church always took measures for people in need of support and assistance. Teaching successive popes and the Second Vatican Council repeatedly undertook the subject. Recalled by Pope Francis option for the poor it can be read in terms of the existential. Disability because it is often perceived as a form of poverty, physical or mental. Therefore, as the Church’s teaching is the actual practice in this topic? Or the community of the Church with disabilities are full members or rather are created for them to certain groups in advance to determine their dysfunctions? This article addresses the issue of intellectual disability as a special space to proclaim the Gospel. Also tries to answer the question whether this space is not a field mission of the Church.